2014
DOI: 10.1111/1467-9817.12029
|View full text |Cite
|
Sign up to set email alerts
|

Validity and sensitivity of the phonics screening check: implications for practice

Abstract: Background Introduced in June 2012, the phonics screening check aims to assess whether 6‐year‐old children are meeting an appropriate standard in phonic decoding and to identify children struggling with phonic skills. Aims We investigated whether the check is a valid measure of phonic skill and is sensitive in identifying children at risk of reading difficulties. Sample We obtained teacher assessments of phonic skills for 292 six‐year‐old children and additional psychometric data for 160 of these children. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 14 publications
1
38
0
Order By: Relevance
“…Each of our measures of oral language (speech perception, phonological awareness, speech articulation accuracy and morphological awareness) significantly differed according to the children's risk status as judged by their teachers. These findings are consistent with other evidence suggesting that teachers are in fact good at judging oral language processing (e.g., Duff, Mengoni, Bailey, & Snowling, 2014). Importantly, children in these schools were actively taught phonological processing, which may have heightened the teachers' sensitivity to children's phonological awareness abilities, making them more easily observed in the classroom.…”
Section: Discussionsupporting
confidence: 89%
“…Each of our measures of oral language (speech perception, phonological awareness, speech articulation accuracy and morphological awareness) significantly differed according to the children's risk status as judged by their teachers. These findings are consistent with other evidence suggesting that teachers are in fact good at judging oral language processing (e.g., Duff, Mengoni, Bailey, & Snowling, 2014). Importantly, children in these schools were actively taught phonological processing, which may have heightened the teachers' sensitivity to children's phonological awareness abilities, making them more easily observed in the classroom.…”
Section: Discussionsupporting
confidence: 89%
“…While other studies have indicated that both pseudo and real word identification fluency are good predictors of reading fluency (e.g. Sisco-Taylor, 2012, p.19;Duff, et al 2014), the issue remains that the rationale for the inclusion of pseudowords in the Y1 phonics Check is not clearly explained, as Clark indicates, and is questionable insofar as it fails to justify what additional value (or, indeed, additional harm) the inclusion of pseudowords would bring to such an assessment.…”
Section: Pseudowords As Predictors Of Children's Reading Skillsmentioning
confidence: 88%
“…Some teachers reported that the test was undiagnostic (see Clark, Oct 2013d, p.15) and revealed no novel assessment information: '91% of respondents felt the Check did not tell them anything they did not already know about the children's reading ability' (ATL, NAHT, NUT, July 2012. See also Duff et al, 2014;NFER, 2014). Many reported that it did not address the particular needs of pupils with ESL, to which the DfE reported that in the first year 'the same percentage as those whose first language was recorded as other than English passed the test ' (DfE, 2013b, p.2).…”
Section: Teachers' Initial Concerns With the Checkmentioning
confidence: 99%
“…Results have implications for practice in terms of choice of reference standard and choice of threshold criterion for children to pass the screening check. Longitudinal data are needed to assess the predictive validity and utility of the check. What is already known about this topic: The importance of phonics in learning to read is widely acknowledged. The phonics screening check was introduced into U.K. schools in 2012 to ensure that all children develop phonic decoding skills. Estimates of the sensitivity and specificity of the phonics screening check, compared with two established ‘reference’ measures, were reported by Duff et al (). What this paper adds: We correct a minor error in the report of the original data by Duff et al (). We draw attention to the importance of including predictive values, alongside sensitivity and specificity, in the evaluation of screening test validity. We also propose an alternative statistic for comparing the two reference measures. We show that applying this further analysis to the data in Duff et al () reveals the following: (i) the numbers of incorrect (false positive and false negative) outcomes in the phonics check and (ii) the marked difference in these numbers depending on the choice of reference measure. Implications for theory, policy or practice: Reports of screening test validity should include positive and negative predictive values. A fundamental consideration for evaluating the validity of the phonics screening check is the choice of reference measure. Longitudinal data are needed to assess the predictive validity and utility of the phonics check. …”
mentioning
confidence: 99%
“…What is already known about this topic: The importance of phonics in learning to read is widely acknowledged. The phonics screening check was introduced into U.K. schools in 2012 to ensure that all children develop phonic decoding skills. Estimates of the sensitivity and specificity of the phonics screening check, compared with two established ‘reference’ measures, were reported by Duff et al (). …”
mentioning
confidence: 99%